Ceftriaxone‐induced drug reaction mimicking acute splenic sequestration crisis in a child with hemoglobin SC disease. Issue 4 (22nd February 2018) - Van Buren, Nancy L.; Gorlin, Jed B.; Reed, Robyn C.; Gottschall, Jerome L.; Nelson, Stephen C.
Abstract : BACKGROUND: Acute splenic sequestration crisis is a complication of sickle cell disease (SCD) occurring when intrasplenic red blood cell (RBC) sickling prevents blood from leaving the spleen, causing acute splenic enlargement. Although typically seen in young children, it has been reported in older children with hemoglobin (Hb)SC disease, eventually resulting in functional asplenia. Ceftriaxone is a frequently used antibiotic of choice for children with SCD, because of its efficacy against invasive pneumococcal disease. CASE REPORT: We report a case of a 9‐year‐old female with HbSC disease, who had a fatal reaction after receiving a dose of ceftriaxone in the outpatient clinic for fever. Her Hb level decreased abruptly from 9.3 to 2.3 mg/dL. RBC clumps with no visible hemolysis were observed in the postreaction sample. Autopsy examination revealed marked splenomegaly with acute congestion and sickled cells in the spleen and liver. Serologic testing revealed a positive direct antiglobulin test with polyspecific antibody, anti‐C3, and anti‐C3d, but negative with anti‐immunoglobulin G. Ceftriaxone‐dependent RBC antibodies were detected in her serum and RBC eluate when tested in the presence of the drug. CONCLUSION: We report a new presentation of ceftriaxone‐induced drug reaction in a patient with SCD mimicking an acute splenic sequestration crisis. Review of the literature for cases of ceftriaxone‐induced drug reactions in pediatric patients revealed nine previously reported cases of ceftriaxone‐induced immune hemolytic anemia in children with SCD since 1995, but none with an initial presentation suggestive of acute splenic sequestration crisis.